Significados y vivencias durante el proceso de envejecimiento y vejez en mujeres trans de la ciudad de Bogotá - Villamizar Fuentes, Alexandra; Duarte Nuñez, Jessica Maris; Monroy Avila, David Sneyder (Universidad Antonio Nariño, 2023)
Aging can be defined as the process through which any being goes through without distinction of race, sex, socioeconomic factor, in which processes are experienced personal physical, physiological, chemical, social and psychological aspects that old age entails. HE reviewed different theories on aging in three scenarios: biological, psychological and adaptive, which allow us to understand that each author has a perception different. In this sense, it is shown that the Colombian system does not present a related to differential approach. It is vitally important to emphasize the experiences during the life trajectory that lead to old age of the trans women of the Organization of Older Trans Women, thereby evidencing the processes of bodily transformation, humanization, support networks, mental health status and health care. This research will use descriptive qualitative methodology, collecting data data through semi-structured interviews in which trans women will give account of the meanings of aging processes to reach old age